2021
DOI: 10.3390/life11050444
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Intake: Are All Children Made of Sugar?

Abstract: Introduction: A healthy diet is characterized by a variety of food and a balanced energy intake, which should accompany every human being since early childhood. Unfortunately, excessive consumption of protein, fat, and lately sugar are very common in developed countries. Sugar intakes are not easily quantifiable and comparable among subjects. Therefore, we decide to analyze dietary patterns in children of different ages and diets (with and without gluten) using a food and nutrient database and a new applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…Therefore, when combined with a high carbohydrate intake, such elimination may impair glycaemic control in children with CD and coexistent type 1 diabetes and increase the risk of overweight and obesity, dyslipidaemia, cardiovascular and liver disease in the general population [ 25 ]. It has been reported that the risk of paediatric obesity and metabolic syndrome can also be further increased by excessive protein intake [ 10 , 23 ]; indeed, our present findings indicate no significant differences between the GFD and control groups. It is therefore recommended that the children should receive dietary counselling to limit carbohydrate and protein intake.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Therefore, when combined with a high carbohydrate intake, such elimination may impair glycaemic control in children with CD and coexistent type 1 diabetes and increase the risk of overweight and obesity, dyslipidaemia, cardiovascular and liver disease in the general population [ 25 ]. It has been reported that the risk of paediatric obesity and metabolic syndrome can also be further increased by excessive protein intake [ 10 , 23 ]; indeed, our present findings indicate no significant differences between the GFD and control groups. It is therefore recommended that the children should receive dietary counselling to limit carbohydrate and protein intake.…”
Section: Discussionsupporting
confidence: 64%
“…However, as also noted previously [ 7 , 8 , 9 ], our findings do not indicate any significant difference in carbohydrate intake between children on gluten-free and gluten-containing diets, suggesting that this imbalance is not exacerbated by GFD. The higher intake may well be attributable to the Polish population, particularly schoolchildren and young adults, following Western dietary habits, which includes foods with high simple sugar levels (e.g., sugar sweetened beverages) [ 23 , 24 ]. Although it was not possible to calculate the GI of the GFD in the CD-affected children in the present study, due to the limited availability of information, it is well known that gluten slows the rate of small bowel starch hydrolysis in the small bowel; as such, dietary gluten elimination may well augment the glycaemic response to carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of preventable diseases and their risk factors is also of major importance from a health policy perspective, as there is a significant cost overrun in health care linked to these disease groups, and as the quality of life deteriorates, the working capacity of individuals is reduced, with an overall negative impact on the country’s economy. In the future, policy measures to promote healthy lifestyles and healthy eating habits and overall health literacy should be a priority [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costs to treat obesity and consequent diseases for the entire population are unbearably high, requiring urgent motivation and guidance to change people’s behaviours, in order to undergo prevention through healthy eating and active lifestyles. Several studies have confirmed the growing trends of very low consumption rates of fruit and vegetables, with high consumption rates of high-fat and energy-dense foods, added sugar food, and sugary drinks, as well as the lack of breakfast among adolescents [ 6 , 7 , 8 ], which worsens the current situation.…”
Section: Introductionmentioning
confidence: 99%